Eficiência da ação do coagulante sulfato de alumínio e cloreto férrico no tratamento de efluente têxtil - Canezim, Rafaela Andressa (2021)
The relevance of the textile industry in the country and in the world is big, since it is a sector that grows and develops more and more over the years. It is responsible for a large part of the world’s water pollution, generating large amounts of effluents that require prior treatment for disposal in the receiving water body. In this context, the present work rated the performance of inorganic coagulants, Aluminum Sulfate and Ferric Chloride in the treatment of textile effluent through the processes of coagulation, flocculation and sedimentation. In this way, triplicate tests were performed using JarTest equipment, with variation of the pH of the effluent in acid, basic and neutral to observe the behavior of the coagulants in each of these situations. The concentrations of aluminum Sulfate and Ferric Chloride used were 4mL.L ¹ and 2 mL.L ¹, respectively. To evaluate this performance the parameters turbidity, total dissolved solids (TDS), electrical conductivity and temperature were analysed. In general, the neutral pH obtained the best result for most of the evaluated parameters, where it can be seen that for the Aluminum Sulfate coagulant it did better results, but showing little difference compared to Ferric Chloride. The removal values found for Aluminum Sulfate were 81,71% for turbidity and 79,12% for Ferric clohride with a final value of 1640 μS cm1 for electrical conductivity and 374,6 ppm for TDS. As for the turbidity parameter, the treatment that was observed the best removal was that of acidic pH with the use of the Ferric Chloride coagulant, followed by Aluminum Sulfate with removals of 93,31% and 92,58%, respectively. Although Aluminum Sulfate with neutral pH has performed better in the analysis of most parameters, an exact conclusion has not been reached as to which coagulant stood out, since each parameter was successful with different treatment features.